(untitled) (Sahayaatra सहयात्रा, 2026)
This article explores the basic knowledge of source law and legalese for legal translation by analyzing the translation of the property law in the National Civil (Code) Act 2017. It examines the basic skills to understand the source Nepali law and language, with legal argot that makes it difficult for general readers. The hermeneutic interpretative method is used to interpret and analyze the source language (SL) text and its equivalent in the target language (TL). This research is based on the proposition that a legal translator needs basic knowledge of the source law, legalese, and lexis for faithful correspondence. It concludes that quality in translation demands basic knowledge of the source law and legalese. From this research, the readers internalize the importance of the source law and language, and analyze the ST linguistically and extralinguistically as pre-translation.